Collateral damage: Hidden impact of the COVID-19 pandemic on the out-of-hospital cardiac arrest system-of-care. (November 2020) - Ball, J; Nehme, Z; Bernard, S; Stub, D; Stephenson, M; Smith, K
Abstract: Aim: Out-of-hospital cardiac arrest (OHCA) during COVID-19 has been reported by countries with high case numbers and overwhelmed healthcare services. Imposed restrictions and treatment precautions may have also influenced OHCA processes-of-care. We investigated the impact of the COVID-19 pandemic period on incidence, characteristics, and survival from OHCA in Victoria, Australia. Methods: Using data from the Victorian Ambulance Cardiac Arrest Registry, we compared 380 adult OHCA patients who received resuscitation between 16th March 2020 and 12th May 2020, with 1218 cases occurring during the same dates in 2017−2019. No OHCA patients were COVID-19 positive. Arrest incidence, characteristics and survival rates were compared. Regression analysis was performed to understand the independent effect of the pandemic period on survival. Results: Incidence of OHCA did not differ during the pandemic period. However, initiation of resuscitation by Emergency Medical Services (EMS) significantly decreased (46.9% versus 40.6%, p = 0.001). Arrests in public locations decreased in the pandemic period (20.8% versus 10.0%; p < 0.001), as did initial shocks by public access defibrillation/first-responders (p = 0.037). EMS caseload decreased during the pandemic period, however, delays to key interventions (time-to-first defibrillation, time-to-first epinephrine) significantly increased. Survival-to-discharge decreased by 50% during the pandemic period (11.7% versus 6.1%; p = 0.002). Survivors per million person-years dropped in 2020, resulting in 35 excess deaths per million person-years. On adjusted analysis, the pandemic period remained associated with a 50% reduction in survival-to-discharge. Conclusion: The COVID-19 pandemic period did not influence OHCA incidence but appears to have disrupted the system-of-care in Australia. However, this could not completely explain reductions in survival.